A STUDY ON CROSS-CULTURAL SHOCKS EXPERIENCED BY BILLY WANG BETWEEN AMERICAN CULTURE AND CHINESE CULTURE IN THE FAREWELL 2019 MOVIE - Seila Odelia Nuandini; Indri Kustantinah (Dharmas Education Journal (DE_Journal), 2022)
In this study, the writer uses a material object namely The Farewell 2019 movie to find out what kind of culture shock was found and its implications. Have an authentic and informative story. For us viewers who are not ethnic Chinese, we get new knowledge about Chinese family traditions which are actually 'saklek' and have important meaning for them. In this study used the descriptive qualitative method. Descriptive studies is a form of studies that indicated to describe phenomena that exist, both natural phenomena and artificial phenomena. The main data of this study was taken from the movie entitled The Farewell 2019. The writer takes the data source by observing each film scene and will capture each scene. The method used in collecting data was the documentation method. In this study, descriptive qualitative approach analysis was used to analyze culture shock in The Farewell 2019 movie. The movie reflects the culture shock of the main character. The writer also found the stages of a person's phase when experiencing culture shock which is divided into four stages; the honeymoon, the hostility, the recovery, and the adjustment. All of them is reflected in the main character, Billy Wang who gets a culture shock in his native China. In cultural implications, The Farewell 2019 movie is reflected in the acceptance that after a person goes through several phases of culture shock and the imply in the movie is starting to accept and learn the culture of other countries, including a form of positive attitude in understanding different cultures, not closing oneself and always open to changes and differences in the surrounding environment.